2004
DOI: 10.1038/sj.mp.4001432
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor gating abnormalities in young males with fragile X syndrome and Fmr1-knockout mice

Abstract: Fragile X syndrome (FXS) is the most common single gene (FMR1) disorder affecting cognitive and behavioral function in humans. This syndrome is characterized by a cluster of abnormalities including lower IQ, attention deficits, impairments in adaptive behavior and increased incidence of autism. Here, we show that young males with FXS have profound deficits in prepulse inhibition (PPI), a basic marker of sensorimotor gating that has been extensively studied in rodents. Importantly, the magnitude of the PPI impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
231
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(271 citation statements)
references
References 39 publications
30
231
9
Order By: Relevance
“…Similar impairments in sensorimotor gating have also been reported in adults with autism 67 or Asperger syndrome. 68 Parallel studies conducted by Frankland et al 66 confirmed that the Fmr1-null mice have enhanced prepulse inhibition of acoustic startle responses, in line with previous findings. 49,63 In addition, the Fmr1-null mice also had enhanced learning in complex operant conditioning tasks.…”
Section: Mouse Models Of Genetic Clinical Disorders With Autism Symptsupporting
confidence: 78%
See 2 more Smart Citations
“…Similar impairments in sensorimotor gating have also been reported in adults with autism 67 or Asperger syndrome. 68 Parallel studies conducted by Frankland et al 66 confirmed that the Fmr1-null mice have enhanced prepulse inhibition of acoustic startle responses, in line with previous findings. 49,63 In addition, the Fmr1-null mice also had enhanced learning in complex operant conditioning tasks.…”
Section: Mouse Models Of Genetic Clinical Disorders With Autism Symptsupporting
confidence: 78%
“…51 This would not explain behavioral changes in the Fmr1-null mice that are opposite to those associated with FXS and autism. For example, Frankland et al 66 reported that human subjects with FXS showed marked deficits in prepulse inhibition of acoustic startle responses. Similar impairments in sensorimotor gating have also been reported in adults with autism 67 or Asperger syndrome.…”
Section: Mouse Models Of Genetic Clinical Disorders With Autism Symptmentioning
confidence: 99%
See 1 more Smart Citation
“…One indication supporting the former possibility is the recent report that PPI is normal in effectively treated, non-manic patients with childhood bipolar disorder (Rich et al, 2005). In additional studies prompted in part by suggested genetic contributions to schizophrenia or related disorders, deficits in PPI have also been identified in children with 22q deletion syndrome (Sobin et al, 2005), young persons with Fragile X syndrome (Frankland et al, 2004), and adults with Asperger's syndrome (McAlonan et al, 2002), seizure disorder (Pouretemad et al, 1998), or Lewy body dementia (Perriol et al, 2005).…”
Section: Sensorimotor Gating Deficits In Psychiatric Disordersmentioning
confidence: 99%
“…The extent to which an animal inhibits the subsequent startle response is thought to reflect the animal's ability to automatically filter out extraneous sensory information . Reduced PPI has been observed in several psychiatric and neurological illnesses, includingFbut not limited toFautism (Perry et al, 2006), Fragile X syndrome (Frankland et al, 2004), panic disorder (Ludewig et al, 2005), manic depression (Perry et al, 2001), obsessive compulsive disorder (Hoenig et al, 2005), Huntingtons' disease (Swerdlow et al, 1995), schizophrenia (Braff et al, 1978), and Tourette's syndrome (Castellanos et al, 1996). PPI deficits are particularly relevant to the study of schizophrenia and Tourette's syndrome because the ability of a drug to increase PPI in rodents predicts the clinical efficacy of medications specifically used to treat these patient populations (Swerdlow and Geyer, 1998;Geyer et al, 2001;Sandor, 2003).…”
Section: Introductionmentioning
confidence: 99%